2013
DOI: 10.1111/lam.12168
|View full text |Cite
|
Sign up to set email alerts
|

Postantibiotic effect and postantibiotic sub-minimum inhibitory concentration effect of valnemulin against Staphylococcus aureus isolates from swine and chickens

Abstract: Significance and Impact of the Study: In this study, valnemulin demonstrated prolonged postantibiotic effects and postantibiotic sub-MIC effects on strains of Staphylococcus aureus. The strains with identical MICs of valnemulin exhibited different PAEs and PA-SMEs. Staphylococcus aureus isolated from different species has little impact on the postantibiotic effect of valnemulin. The result suggests a longer dosing interval while formulating a daily administration dosage, and it may play a valuable role of valn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…In comparison with the contribution of PAE, PA-SME possibly reveals more useful clinical information as a period of subinhibitory concentrations would always exist in vivo, while the drug concentrations in plasma would be less than the MIC because of the process of elimination. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the contribution of PAE, PA-SME possibly reveals more useful clinical information as a period of subinhibitory concentrations would always exist in vivo, while the drug concentrations in plasma would be less than the MIC because of the process of elimination. 24 …”
Section: Discussionmentioning
confidence: 99%
“…It could also be observed that amphenmulin showed potent activity against all Gram-positive bacteria, except E. faecalis (ATCC 29212), and pretty weak activity against the Gram-negative bacteria E. coli (ATCC 25922) and S. typhimurium (ATCC 14028). Previous study has shown that valnemulin only showed bacteriostatic effect on Staphylococcus aureus [25]. According to the time-kill curve, amphenmulin belongs to bacteriostatic agents as well.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, amphenmulin displayed a concentration-independent PAE and performed a comparable or longer PAE than tiamulin against MRSA. It indicated that amphenmulin may possess longer dosing intervals, fewer adverse effects, and lower costs while formulating a daily administration dosage [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have clearly shown that the area under the concentration–time curve (AUC) divided by the minimum inhibitory concentration (MIC) (AUC/MIC) is the most important predictive parameter of clinical and microbiological response for glycopeptides (Revilla et al ., ) and quinolones (Tanigawara et al ., ). Previous studies for valnemulin focused on its structure (Tang et al ., ), antibacterial mechanism (Zhang et al ., ), PK (Yuan et al ., ; Xiao et al ., ), antimicrobial activity (Zhao et al ., ) and resistance (Long et al ., ). However, dosage regimen for valnemulin based on PK/PD principles has not been carefully considered.…”
Section: Introductionmentioning
confidence: 99%